2002
DOI: 10.1016/s0375-9474(01)01253-2
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic pionic effects in quasielastic electron scattering

Abstract: The impact of relativistic pionic correlations and meson-exchange currents on the response functions for electromagnetic quasielastic electron scattering from nuclei is studied in detail. Results in first-order perturbation theory are obtained for one-particle emission electronuclear reactions within the context of the relativistic Fermi gas model. Improving upon previous analyses where non-relativistic reductions of the currents were performed, here a fully relativistic analysis in which both forces and curre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
79
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(85 citation statements)
references
References 41 publications
6
79
0
Order By: Relevance
“…Similar effects were also found at higher momentum transfers using a relativistic Fermi gas (RFG) model [5,6]. The same trend is confirmed by the results of the present study for q = 1 GeV/c, as shown in the upper panel of Fig.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Similar effects were also found at higher momentum transfers using a relativistic Fermi gas (RFG) model [5,6]. The same trend is confirmed by the results of the present study for q = 1 GeV/c, as shown in the upper panel of Fig.…”
supporting
confidence: 91%
“…An exhaustive analysis of (e, e ) world data demonstrated the scaling at energy transfers ω below the quasielastic (QE) peak [1,2], namely the independence of the reduced cross sections on the momentum transfer (first-kind scaling) and on the nuclear target (second-kind scaling) when plotted versus the appropriate scaling variable. It is well known that at energies above the QE peak scaling is violated in the transverse (T ) channel by effects beyond the impulse approximation: inelastic scattering [3,4], correlations, and meson-exchange currents (MEC) in both the one-particle one-hole (1p-1h) and two-particle two-hole (2p-2h) sectors [5][6][7][8].In contrast, the available data for the longitudinal (L) response are compatible with scaling throughout the QE region and permitted [9] the extraction of a phenomenological scaling function f L . In recent work [10][11][12] it was shown that only a few models [the relativistic mean field (RMF), the semirelativistic (SR) approach with Dirac-equation-based (DEB) and a "BCS-like" model] are capable of reproducing the detailed shape of f L , while other models fail to reproduce the long tail appearing at high ω. Theses models effectively account for the major ingredients needed to describe the (e, e ) responses for intermediate-to-high momentum transfers, namely relativistic effects and an appropriate description of the effective final-state interactions (FSI).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The symbol χ specifies neutrino-induced reactions (χ = +) or antineutrinoinduced reactions (χ = −), and the term σ 0 depends on the Fermi constant and the Cabibbo angle (see [13] for its explicit expression). The kinematic factors v K andv K come solely from the electromagnetic and weak leptonic tensors, respectively, and their explicit expressions can be found in [4,8,13]. The electromagnetic R K and weakR K response functions contain the whole dependence on the nuclear vertex coupling and are expressed by taking the appropriate components of the nuclear tensor [4,8,13].…”
Section: Inclusive Quasielastic Lepton Scattering Formalism: the mentioning
confidence: 99%
“…The kinematic factors v K andv K come solely from the electromagnetic and weak leptonic tensors, respectively, and their explicit expressions can be found in [4,8,13]. The electromagnetic R K and weakR K response functions contain the whole dependence on the nuclear vertex coupling and are expressed by taking the appropriate components of the nuclear tensor [4,8,13]. This involves the matrix elements of the virtual photon or charged boson interaction with the nuclear electromagnetic or weak current.…”
Section: Inclusive Quasielastic Lepton Scattering Formalism: the mentioning
confidence: 99%